JURIDICAL ANALYSIS OF JUDGES' CONSIDERATIONS IN IMPOSING SANCTIONS MINIMUM PENALTY IN CORRUPTION - Andria Hariza Nugraha; Tajuddin Noor; Panca Sarjana Putra (Jurnal Ilmiah METADATA, 2026)
The imposition of a criminal under a special minimum criminal sanction in Law Number 31 juncto Law Number 20 of 2001 concerning the eradication of corruption crimes, where the imposition of a criminal under the special minimum criminal sanction in the crime of corruption is basically unjustifiable based on legal justice. The results of the study show that the judge's consideration in imposing a criminal sentence on the perpetrators of corruption crimes according to the Supreme Court Decision Number 3280 K/Pid.Sus/2024 is the existence of elements of state financial losses or the state economy as a result of the criminal acts of corruption so that the defendant was sentenced to imprisonment for 2 (two) years and 6 (six) months and a fine of Rp. 100,000,000,- (one hundred million rupiah).